Decline in Literacy and Incident AD Dementia Among Community-Dwelling Older Persons. (October 2018) - Yu, Lei; Wilson, Robert S.; Han, S. Duke; Leurgans, Sue; Bennett, David A.; Boyle, Patricia A.
Objective: To quantify longitudinal change in financial and health literacy and examine the associations of declining literacy with incident Alzheimer's disease (AD) dementia and mild cognitive impairment (MCI).Method: Data came from 799 participants of an ongoing cohort study. Literacy was measured using a battery of 32 questions. Clinical diagnoses were made annually following uniform structured procedures. The associations of declining literacy with incident AD dementia and MCI were tested using a joint model for longitudinal and time-to-event data.Results: We observed an overall decline in total literacy score over up to 6 years of follow-up ( p < .001). Faster decline in literacy was associated with higher risks for incident AD dementia (hazard ratio = 4.526, 95% confidence interval = [2.993, 6.843], p < .001) and incident MCI (hazard ratio = 2.971, 95% confidence interval = [1.509, 5.849], p = .002).Discussion: Declining literacy among community-dwelling older persons predicts adverse cognitive outcomes and serves as an early indicator of impending dementia.